**CAN SOMEONE PLEASE SHOW STEPS TO SOLVE 3X3 WITHOUT CRAMER’S RULE THANK YOU LUVVS!!!**

x-y+2z=0

3x+z=11

-x+2y=0

**Answer:**

x-y+2z=0…eqation1

3x+z=11…eqation2

-x+2y=0…eqation 3

simply eqation 2

as z=11-3x…put it in eqation1

eqation1 becomes

x-y+2(11-3x)=0

x-y+22-6x=0

-5x-y=-22

multiply by 2 on both sides

-10x-2y=-44…eqation4

Now Add eqation 3 and eqation 4 you will get

-11x=-44

x=4

so z=11-3x

z=11-3*4
z=11-12
z=-1
put the value of X and Y in eqation 1
x-y+2z=0
4-y+2*(-1)=0

4-y-2=0

-y+2=0

-y=-2

multiply BY -1 on both sides

y=2

So value of x=4 , y=2 ,z=-1